Development of the Incense Business Group through Business Management in Angantaka Village, Abiansemal, Badung - Ningsih, Ni Luh Anik Puspa; Nitiwidari, Dewa Ayu Putu; Trisnadewi, Anak Agung Ayu Erna (PT FORMOSA CENDEKIA GLOBAL, 2024)
The MSME sector is expected to become a new source of national economic strength during crises. To achieve this, the government should focus on human resources and management. Limited innovation within SMEs has led to stagnant growth, and financial issues often hinder productivity. One community service project is the Suputra herbal incense SME in Angantaka Village, Abiansemal, located 11.2 km from Universitas Warmadewa. According to Mrs. Ayu, the main challenge is limited business management capabilities. A lack of business management knowledge impedes growth. The partnership program aims to increase sales and improve financial practices through three activities: financial management assistance, production management, and creating a product catalog. The results show structured bookkeeping, reduced errors, enhanced management efficiency, and the development of a product catalog.